2022
DOI: 10.3390/bs13010034
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Emotional Valence and Social Media Content Engagement Behaviors in Pandemic Diaries: An Analysis Based on Microblog Texts

Abstract: The effects of the COVID-19 pandemic are individualized, which means that our emotions and behaviors would experience changes of different degrees. These changes have led to subtle connections within the social media context. This study concentrates on pandemic diaries posted on microblog sites during the lockdown period in China and explores the association between gender, emotional valence in diaries, and social media content engagement behaviors. Through computational methods, this study found that males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In English-speaking samples, researchers have found that, while in pre-schoolers, there are no differences between boys and girls in the use of emotion words during peer interactions (Fabes et al, 2001 ), 6- (Tenenbaum et al, 2011 ) and 13-year-old girls (Aldrich & Tenenbaum, 2006 ) use more emotion labels than boys when interacting with others. Also, a recent investigation on social media content in Chinese individuals shows that women write more positively laden words than men (Feng & Ivanov, 2022 ), a finding that is confirmed by the analysis of Wikipedia editors’ comments in English (Gallus & Bhatia, 2020 ). However, one interesting aspect of studying the affective lexicon to understand the nature of gender differences in emotion is that it can be studied as a function of space (i.e., in relation to various cultures) and time (i.e., in relation to societal evolution).…”
mentioning
confidence: 75%
“…In English-speaking samples, researchers have found that, while in pre-schoolers, there are no differences between boys and girls in the use of emotion words during peer interactions (Fabes et al, 2001 ), 6- (Tenenbaum et al, 2011 ) and 13-year-old girls (Aldrich & Tenenbaum, 2006 ) use more emotion labels than boys when interacting with others. Also, a recent investigation on social media content in Chinese individuals shows that women write more positively laden words than men (Feng & Ivanov, 2022 ), a finding that is confirmed by the analysis of Wikipedia editors’ comments in English (Gallus & Bhatia, 2020 ). However, one interesting aspect of studying the affective lexicon to understand the nature of gender differences in emotion is that it can be studied as a function of space (i.e., in relation to various cultures) and time (i.e., in relation to societal evolution).…”
mentioning
confidence: 75%
“…For example, Zhu et al revealed the anxiety difference between six types of quarantine (e.g., forced quarantine at home and centralized quarantine) [79]. Another stream of research centered on the changes of emotions where interesting changing patterns usually hide [17,30,50]. For example, Cao et al uncovered emotional evolution during each phase of Wuhan lockdown including the incubation phase, explosive phase, declining phase and stable phase [17].…”
Section: Emotional Disclosure On Social Media In Quarantinementioning
confidence: 99%
“…However, this online exposure also brought unwanted attention and censorship. Previous studies primarily focused on Wuhan, including lockdown diaries in Wuhan or nationwide quarantine diaries during the outbreak period in Wuhan [30]. Nevertheless, this diary form exists nationwide, and the quarantine measures have been in place for an extended period of time.…”
Section: Online Diaries On Social Media In Quarantinementioning
confidence: 99%
See 1 more Smart Citation
“…These measures have achieved remarkable results in containing the spread of the epidemic. However, COVID-19 has also significantly impacted the daily life and mental health of the population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%